ORIGIN, DIRECTION, AND RATE OF MODERN COMPRESSION OF THE CENTRAL TIEN SHAN (KYRGYZSTAN) - Abdrakhmatov K.E.; Weldon R.; Thompson S.; Burbank D.; Rubin Ch.; Miller M.; Molnar P. (My University, 2001)
We have determined slip rates on the most active reverse faults, reconstructed an extensive preorogenic erosion surface, constructed local and regional cross sections, and dated syntectonic Tertiary sedimentary rocks by magnetostratigraphy along a north-south transect that spans the Kyrgyz portion of the west-central Tien Shan. The cumulative Late Quaternary shortening rate along this transect is 10 mm/yr. The trabsect consists of five major fault zones, and the most active faults lie in the interior of the range. Using geometric models developed in other regions of basement-involved determination, we estimate shortening during the Late Cenozoic at 35-80 km. Apparent simultaneous onset of sedimentary basins (at least 3 major basins) about 12 Ma BP is interpreted to mark the onset of the current orogeny. Given the current shortening rate of about 10 mm/yr, measured across active faults and by GPS, we infer that the rate increased with time. We assumed accelerated shortening and have shown that it has always been of similar style, dominated by north-south shortening across east-west trending basement-involved reverse faults. Deformations were localized in five zones, which border the largest and deepest Tertiary basins, show the greatest structural relief, and contain the currently most active faults.
Keywords: Quaternary; Cenozoic; Cenozoic::Quaternary; Cenozoic; Кайнозой::Четвертичная; Кайнозой